2018
DOI: 10.3389/fpsyg.2018.00678
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Link Between Cognitive Abilities and Speech Recognition in the Elderly Under Different Listening Conditions

Abstract: Elderly listeners are known to differ considerably in their ability to understand speech in noise. Several studies have addressed the underlying factors that contribute to these differences. These factors include audibility, and age-related changes in supra-threshold auditory processing abilities, and it has been suggested that differences in cognitive abilities may also be important. The objective of this study was to investigate associations between performance in cognitive tasks and speech recognition under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 62 publications
2
33
3
1
Order By: Relevance
“…14 However, we found that older listeners did not necessarily show a stronger association between LS and speech recognition in harder conditions (sentences with multi-talker noise vs sentences with multi-talker noise and TC). These results are not consistent with the findings from the ELU-model 43 that predicted higher involvement of working memory under adverse listening conditions for speech recognition, but consistent with recent studies 24,44 that included participants with a narrow age range or the control for age.…”
Section: Systematic Approach To the Association Between Auditory Workcontrasting
confidence: 65%
“…14 However, we found that older listeners did not necessarily show a stronger association between LS and speech recognition in harder conditions (sentences with multi-talker noise vs sentences with multi-talker noise and TC). These results are not consistent with the findings from the ELU-model 43 that predicted higher involvement of working memory under adverse listening conditions for speech recognition, but consistent with recent studies 24,44 that included participants with a narrow age range or the control for age.…”
Section: Systematic Approach To the Association Between Auditory Workcontrasting
confidence: 65%
“…In the above-mentioned study conducted by Humes, for example, the explained variance for monosyllabic word recognition scores in quiet and in noise fell to < 5% when the stimuli were spectrally shaped prior to presentation to simulate the effect of a hearing aid. However, in general, a residual correlation is still observed between PTA and performance, especially in the most demanding listening situations (up to ~ 50% of explained variance in a spatialized sentence comprehension task using two simultaneous linguistic and non-linguistic maskers; Nuesse et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although this body of evidence points toward an overall role of suprathreshold auditory processes and cognition in the speech-in-noise comprehension deficit in the elderly, it is worth noting that the precise mechanisms involved are still unclear. In particular, no single cognitive function appeared as significant across all studies (Akeroyd, 2008 ) and several researchers were unable to find a significant link between speech recognition in noise and the cognitive abilities they measured in their pool of participants (Schoof and Rosen, 2014 ; Meister et al, 2015 ; Lopez-Poveda et al, 2017 ; Nuesse et al, 2018 ). Similarly, studies are not always consistent on the role of auditory temporal processing skills on aging speech perception.…”
Section: Introductionmentioning
confidence: 99%
“…These tasks have the obvious merit of providing an assessment with the face validity of speech perception but may lack standardization and, therefore, clinical utility. Word and sentence stimuli also rest heavily on higher order cognitive processing, particularly in the language, attention, and memory domains (Kaandorp, Smits, Merkus, Festen, & Goverts, 2017; Nuesse, Steenken, Neher, & Holube, 2018). Because they involve speech stimuli, they also need to be adapted to and normalized for different languages, an arduous and imprecise process.…”
Section: Introductionmentioning
confidence: 99%